Insight into the spoilage heterogeneity of meat-borne bacteria isolates with high-producing collagenase - Haodong Wang; Liangting Shao; Jinhao Zhang; Xinglian Xu; Jianjun Li; Huhu Wang (Food Science and Human Wellness)
Chilled chicken is inevitably contaminated by microorganisms during slaughtering and processing, resulting in spoilage. Cutting parts of chilled chicken, especially wings, feet, and other skin-on products, are abundant in collagen, which may be the primary target for degradation by spoilage microorganisms. In this work, a total of 17 isolates of spoilage bacteria that could secrete both collagenase and lipase were determined by raw-chicken juice agar (RJA) method, and the results showed that 7 strains of Serratia, Aeromonas, and Pseudomonas could significantly decompose the collagen ingredients. The gelatin zymography showed that Serratia liquefaciens (F5) and Pseudomonas saponiphila (G7) had apparent degradation bands around 50 kDa, and Aeromonas veronii (G8) and Aeromonas salmonicida (H8) had a band around 65 and 95 kDa, respectively. The lipase and collagenase activities were detected isolate-by-isolate, with F5 showing the highest collagenase activity. For spoilage ability on meat in situ, F5 performed strongest in spoilage ability, indicated by the total viable counts, total volatile basic nitrogen content, sensory scores, lipase, and collagenase activity. This study provides a theoretical basis for spoilage heterogeneity of strains with high-producing collagenase in meat.